Getting on the Same Page: Consolidating Terminology to Facilitate Cross-Disciplinary Health-Related Blast Research - Belding, Jennifer N.; Egnoto, Michael; Englert, Robyn M.; Fitzmaurice, Shannon; Thomsen, Cynthia J. (Frontiers in Neurology, 2021)
The consequences of blast exposure (including both high-level and low-level blast) have been a focal point of military interest and research for years. Recent mandates from Congress (e.g., National Defense Authorization Act for Fiscal Year 2018, section 734) have further accelerated these efforts, facilitating collaborations between research teams from a variety of disciplinary backgrounds. Based on findings from a recent scoping review, we argue that the scientific field of blast research is plagued by inconsistencies in both conceptualization of relevant constructs and terminology used to describe them. These issues hamper our ability to interpret study methods and findings, hinder efforts to integrate findings across studies to reach scientific consensus, and increase the likelihood of redundant efforts. We argue that multidisciplinary experts in this field require a universal language and clear, standardized terminology to further advance the important work of examining the effects of blast exposure on human health, performance, and well-being. To this end, we present a summary of descriptive conventions regarding the language scientists currently use when discussing blast-related exposures and outcomes based on findings from a recent scoping review. We then provide prescriptive conventions about how these terms should be used by clearly conceptualizing and explicitly defining relevant constructs. Specifically, we summarize essential concepts relevant to the study of blast, precisely distinguish between high-level blast and low-level blast, and discuss how the terms acute, chronic, exposure, and outcome should be used when referring to the health-related consequences of blast exposure.